Simply irresistible - 527251 Shalvis, Jill; Copyright Paperback Collection (Library of Congress) DLC (New York, NY. : Forever, 2010)
Maddie Moore's whole life needs a makeover. In one fell swoop, Maddie loses her boyfriend (her decision) and her job (so not her decision). But rather than drowning her sorrows in bags of potato chips, Maddie leaves L.A. to claim the inheritance left by her free-spirited mother-a ramshackle inn nestled in the little coastal town of Lucky Harbor, Washington. Starting over won't be easy. Yet Maddie sees the potential for a new home and a new career-if only she can convince her two half-sisters to join her in the adventure. But convincing Tara and Chloe will be difficult because the inn needs a big makeover too. The contractor Maddie hires is a tall, dark-haired hottie whose eyes-and mouth-are making it hard for her to remember that she's sworn off men. Even harder will be Maddie's struggles to overcome the past, though she's about to discover that there's no better place to call home than Lucky Harbor.